1967
DOI: 10.1103/physrev.162.56
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Scattering from Atomic Oxygen and Photodetachment fromO

Abstract: A method developed by Temkin to allow for polarization effects in low-energy scattering of electrons from atoms has been extended to include all direct contributions from the polarized orbitals and the exchange contribution from the most important type of polarized orbital. The analysis has been applied to atoms with configurations ls 2 2s 2 2p Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1969
1969
2010
2010

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…We used recent stopping-power data 4 "" 6 and data obtained in this laboratory. 7 The ionization cross sections in absolute units are calculated by normalizing our data to the ionization cross section o^= 53 b reported by Khan et al? for protons at 100 keV.…”
Section: Resultsmentioning
confidence: 99%
“…We used recent stopping-power data 4 "" 6 and data obtained in this laboratory. 7 The ionization cross sections in absolute units are calculated by normalizing our data to the ionization cross section o^= 53 b reported by Khan et al? for protons at 100 keV.…”
Section: Resultsmentioning
confidence: 99%
“…Henry [4] also determined the static dipole polarizability of atomic oxygen. He extended the method developed by Temkin [5] to include all direct contributions from the polarized orbitals and the exchange contribution from the most important type of polarized orbital.…”
Section: Introductionmentioning
confidence: 99%
“…At lower energy, branching ratios between the fine structure components of the O( 2 P J ) → O( 3 P J ) transitions have been studied [6,7,9]. On the theoretical side, some studies around 266 nm have only reported the total photodetachment cross section [15][16][17][18][19], while partial channel-resolved cross sections have indeed also been presented in several calculations [20][21][22][23] allowing a direct comparison to the present experiment. Thus, the ratio 1 D : 3 P after detachment has so far been calculated to ∼0.8 [20] (from their Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Under these aspects the photodetachment process has been the subject of both experimental [2][3][4][5][6][7][8][9][10][11][12][13][14] and theoretical [3,[15][16][17][18][19][20][21][22][23][24][25] investigations for more than half a century.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation